THE EVALUATION OF DANA DESA (The Studi is the Role of Badan Permusyawaratan Desa in Monitoring the Management of Dana Desa in Desa Garung Kecamatan Sambeng Kabupaten Lamongan) - Yohanes Fritantus (AIBPM Publisher, 2019)
This studi to aims to analyze the role of Badan Permusyawaratan Desa in monitoring the management of Dana Desa and analyze the obstacle faced by the Badan Permusyawaratan Desa (BPD) in Desa Garung, Kecamatan Sambeng, Kabupaten Lamongan. The research method used guidance with interview, observation and documentasi. The results of the study that the role of the Badan Permusyawaratan Desa (BPD) in overseeing the management of Dana Desa is divided into each process, namely the Planning stage, Implementation, and reporting. Constraints faced include, the absence of a work program, inadequate measurement of performance, no corrective action taken to prevent irregularities repeatedly. In addition to the three aspects above, the findings in this study, there are aspects that most contribute to the role of the Badan Permusyawaratan Desa in overseeing the management of Dana Desa, namely human competence (HR), budget, facilities and infrastructure, and work methods of the organization.